Adjuvant chemotherapy in resected colon cancer: When, how and how long?. (September 2019) - Gelibter, Alain J.; Caponnetto, Salvatore; Urbano, Federica; Emiliani, Alessandra; Scagnoli, Simone; Sirgiovanni, Grazia; Napoli, Valerio M.; Cortesi, Enrico
Abstract: The benefit of adjuvant chemotherapy has been clearly established in the adjuvant setting for node-positive colon cancer. A number of trials in the adjuvant setting have analyzed the efficacy of multiple-agent combinations, including irinotecan, oxaliplatin, bevacizumab and cetuximab. Only oxaliplatin added to fluorouracil/capecitabine has been shown to be superior beyond a fluropyrimidine alone in the adjuvant setting. As such, standard treatment options include fluorouracil (FU) or capecitabine with or without oxaliplatin. However, oxaliplatin is associated with cumulative dose-dependent neurotoxicity, characterized by distal or perioral paresthesias or dysesthesias; for this reason, in this review we discuss the results of the International Duration Evaluation of Adjuvant Chemotherapy (IDEA) trial. The IDEA trail is the largest prospective clinical trial ever conducted in colorectal cancer, wherein patients were treated with either 3 months or 6 months of adjuvant chemotherapy. In the era of cancer gene expression–based subtyping, the Colorectal Cancer Subtyping Consortium has proposed a four-subgroup molecular classification system for colorectal cancer, consisting of CMS1 (immune), CMS2 (canonical), CMS3 (metabolic) and CMS4 (mesenchymal). In this review, we present and analyze the available data on efficacy and toxicity of the combination regimen approved for treatment of resected colon cancer, and discuss the questions of when, how and how long we need to treat such patients. Abstract : Core tip: The benefit of adjuvant chemotherapy has been clearly established in the adjuvant setting for node-positive colon cancer. A number of trials in the adjuvant setting have analyzed the efficacy of multiple-agent combinations, including fluorouracil, capecitabine, irinotecan, oxaliplatin, bevacizumab and cetuximab. In this review, we present and analyze the available data on efficacy and toxicity of the combination regimen approved for treatment of resected colon cancer, and discuss the questions of when, how and how long we need to treat such patients.